Time Course and Predictors of Worsening Tricuspid Regurgitation Following Right Ventricular Lead Implantation. (November 2020) - Markman, Timothy M.; Kuo, Ling; Mustin, Evan; Amankwah, Nigel A.; Supple, Gregory E.; Dixit, Sanjay; Nazarian, Saman; Arkles, Jeffery; Hyman, Matthew; Lin, David; Epstein, Andrew E.; Santangeli, Pasquale; et al.
Abstract : Supplemental Digital Content is available in the text.